2022
DOI: 10.1002/advs.202202201
|View full text |Cite
|
Sign up to set email alerts
|

Triple Conductive Wiring by Electron Doping, Chelation Coating and Electrochemical Conversion in Fluffy Nb2O5 Anodes for Fast‐Charging Li‐Ion Batteries

Abstract: High‐rate anode material is the kernel of developing fast‐charging lithium ion batteries (LIBs). T–Nb2O5, well‐known for its “room and pillar” structure and bulk pseudocapacitive effect, is expected to enable the fast lithium (de)intercalation. But this property is still limited by the low electronic conductivity or insufficient wiring manner. Herein, a strategy of triple conductive wiring through electron doping, chelation coating, and electrochemical conversion inside the microsized porous spheres consisting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…[39] The O 1s spectrum can be detected to two peaks of 528.70 and 530.45 eV in Figure 4f, which are due to the lattice oxygen in Ti-O bond and the adsorbed oxygen in Nb-O species. [40,41] In the voltage range of 0.01-3.0 V, the galvanostatic chargedischarge (GCD) curves of LZTO and LZTNO samples at 0.1 C (1 C = 229 mA g −1 ) are tested and shown in Figure 5. All samples have two discharge platforms at about 0.5 and 1.5 V. It was reported that the former is originated both from the intercalation reaction and the pseudocapacitance, while the latter is mainly attributed to the pseudocapacitance.…”
Section: Resultsmentioning
confidence: 99%
“…[39] The O 1s spectrum can be detected to two peaks of 528.70 and 530.45 eV in Figure 4f, which are due to the lattice oxygen in Ti-O bond and the adsorbed oxygen in Nb-O species. [40,41] In the voltage range of 0.01-3.0 V, the galvanostatic chargedischarge (GCD) curves of LZTO and LZTNO samples at 0.1 C (1 C = 229 mA g −1 ) are tested and shown in Figure 5. All samples have two discharge platforms at about 0.5 and 1.5 V. It was reported that the former is originated both from the intercalation reaction and the pseudocapacitance, while the latter is mainly attributed to the pseudocapacitance.…”
Section: Resultsmentioning
confidence: 99%
“…The coating layer not only strengthens the charge transport pathways, but also shows abundant specific surfaces and provides more reactive active sites. 162…”
Section: Electrode Designmentioning
confidence: 99%
“…40 The excellent electrochemical properties of the Nb-based layered oxide mean that the Nb ion is a key element for improving structural and electrochemical properties. 41,42 In addition, recent research has proved that Nb ions are one of the most promising doping elements because they can enhance the structural stability and electrical conductivity of conventional layered cathode materials. [43][44][45][46] Nb doping of Ni-rich layered oxides can reduce the charge-transfer resistance and improve the rate capability.…”
Section: Irreversible Structural Transition and Voltage Decay During ...mentioning
confidence: 99%